An innovative structural insulated panel (SIP) : evaluation of durability properties and structural performance / Muhamad Alias Ghazali Baharudin and Md Azree Othuman Mydin - Baharudin, Muhamad Alias Ghazali; Othuman Mydin, Md Azree (2018)
These days, the buildings we use consume significant quantities of materials and energy to build, and during their operational life. One technology that can improve building performance is structural insulated panel (SIPs) construction. SIPs are a high-performance building system for residential and light commercial construction. Hence this research will explore the idea on the development of this panels consist of an insulating foamcrete as a core sandwiched between two structural facings, by using the fiber cement board & magnesium oxide board. The main objective of this study is to observe and determine the structural performance of foamcrete in-filled fiber cement board and magnesium oxide board. For fiber cement board, there two thickness which is 8mm and 9mm, so do the MgO board which is the 6mm and 9mm thickness. There are 8 sets of each board for every thickness. To fabricate the core sandwich between two structural facings, C-channel steel is used. This metal framing channel is cold formed on modern rolling machines from low carbon steel manufactured. A continuous slot provides the ability to make attachments at any point. Then this C-channel are being placed at both sides if the board. After that, the 2 inches loose self-drill fiber cement screws are used to make sure all this member been held together. The spacing of the screw is 100mm with the 50mm start point from the top. The densities of the infill material are 1000kg/m3 and 1400kg/m3 . The results have illustrated that SIPs perform as an effective composite material possessing considerable strength and stiffness necessary to sustain required design loads. The creep effects under a series of axial compression loads (much higher than the normal intended loading) are negligible and the panel recovered after load removal. Also, there was no de-bonding or bulging of the boards